The Impact of Employment Social Security Implementation on the Economy of Bali Province in Indonesia - Sudarsana, Rajwa Rajendra; Pasaribu, Andri Ronaldo; Suryanta, Barli (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2024)
The implementation of Employment Social Security is a form of government responsibility to protect all workers in Indonesia from the risks arising from work. It is necessary to know the impact of the implementation of Employment Social Security on the economy to create an effective Employment Social Security system. This study aims to determine the effect of BPJS Ketenagakerjaan's implementation of Employment Social Security on the economy of Bali Province, especially through increased consumption and investment. This research is expected to be a reference for relevant parties to organize effective Employment Social Security in Indonesia. Using a qualitative method with a literature review approach, this research utilizes secondary data from various sources related to the economy and BPJS Ketenagakerjaan programs, such as Old-Age Security, Employment Injury Security, Death Security, Pension Security, And Unemployment Benefit. The results of this study show that the Employment Social Security program contributes significantly to the economy through consumption and investment stability. These programs can support labor productivity and create a more conducive investment climate. This research emphasizes the importance of policies taken by relevant parties to support the effectiveness of the Employment Social Security program in achieving community welfare and a sustainable economy. This can be the basis for the government, BPJS Ketenagakerjaan, and academics to improve future Employment Social Security policies and programs.